CAUSATIVE FACTORS OF CONSTRUCTION WASTE GENERATION IN MALAYSIA - Ismail Abdul Rahman; Sasitharan a/l Nagapan (Penerbit UTHM, 2015)
This is a research book based on a study conducted to identify the significant causative factors to construction waste generation in Malaysia construction industry. This book describes the research process which includes data analysis in a systematic manner and is organised in four chapters as follows: Chapter 1: Concern of waste generation in construction industry. It covers the classification of the wastes, causes and effects of the generated wastes and also the disposal issues. Chapter 2: Identification on causative factors of construction wastes generation. These factors are identified from previous researches related to construction waste that were carried. Chapter 3: Questionnaire survey on identifying the significant causative factors of construction waste generation in Malaysia construction industry. It describes the design of the questionnaire, implementation of the survey and also the analysis of the collected data. Chapter 4: Development of structural equation model which indicates the structural relationship of causative factors toward the construction waste generation using the multivariate approach.